2018
DOI: 10.1055/s-0038-1667193
|View full text |Cite
|
Sign up to set email alerts
|

Terminal end Variations and Common Pathological Abnormalities of the Basilar Artery among the Ugandan Population: a Human Autopsy Study

Abstract: Introduction Morphological variations at the basilar artery terminal end are documented risk factors for cerebral vascular complications like atherosclerosis, thromboembolisms, and aneurysms that further predispose to fatal arterial occlusions. Pathological abnormalities of the basilar artery are usually ignored on diagnosis in third world countries despite their role in brain ischemia. There is a paucity of literature on the gross anatomy of cerebral vasculature in the Ugandan population. Therefore, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…In the present study, triplication was observed in 4.9% of the cases, all were right unilateral SCAs arising from the BA. This finding is slightly lower than the reported cases of 6.1% by Nagawa et al (2018) in a Ugandan black population. On the other hand, the present study finding is almost comparable with the study done by Gunnal et al (2014) who reported triplication at the rate of 5.29%.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In the present study, triplication was observed in 4.9% of the cases, all were right unilateral SCAs arising from the BA. This finding is slightly lower than the reported cases of 6.1% by Nagawa et al (2018) in a Ugandan black population. On the other hand, the present study finding is almost comparable with the study done by Gunnal et al (2014) who reported triplication at the rate of 5.29%.…”
Section: Discussioncontrasting
confidence: 75%
“…Nagawa et al (2018), who reported the origin of the SCA as a single vessel in 51.3% in a black Ugandan population. However, these results were contrary to the findings of Ogeng'o et al(2015) who reported a higher rate of single origin of the SCA from the BA with a frequency of 72.1% in a black Kenyan population.In the current study, the SCA took origin from the PCA in 5.7% of the cases.…”
mentioning
confidence: 99%
“…Morphological patterns of the basilar artery furcation are consistent with other studies[23,24] and the present study. BA: basilar artery; PComA: posterior communicating artery; PCA: posterior cerebral artery; fPCA: fetal type of posterior cerebral artery; SCA: superior cerebellar artery; aP: artery of Percheron.…”
supporting
confidence: 93%
“…Gunnal et al described the pentafurcations of the BA by including double SCAs in the counts and without distinguishing the origins of SCAs as collateral/terminal/cerebral types [23]. Similarly, Nagawa et al (2018) found penta-and hexafurcations of BA determined by double or triple SCAs, but they did not discriminate SCAs' exact sites of origin [24]. et al described the situations with an absent P1 segment as non-furcation, making the SCA appear on that side of terminal type 2, with the contralateral P1 segment inserted medially at the apex of AB [23]; this morphology corresponds to the C (1 + 2) and G (2 + 3) types of bilateral combinations in the present study and should be correlated to certain furcations of the BA.…”
Section: Discussionmentioning
confidence: 99%